Orszak Dionizosa: Waza Townleya i jej poznańskie kopie - Rosół, Rafał (Collectanea Philologica, 2021)
At the main entrance to the Adam Mickiewicz Park in Poznań, there are two identical stone vases with ancient motives. The author indicates that they are not merely neoclassical works from the beginning of the 20th century, but copies of the famous Townley Vase dating back to the Roman times. Then, he focuses on the retinue of Dionysus on the main frieze of the vase and discusses all ten figures occurring in it.